Fundamental statistics for the behavioral sciences - Howell, David C. (Thomson/Wadsworth, 2008)
This book provides an understanding of the logic behind the statistics: why and how certain methods are used rather than just doing techniques by rote. It contains an abundance of real data and research studies as a base and moves through an analysis of data.